(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article examines the issues of developing the country’s insurance system using Islamic finance instruments. The basic principles of the Takaful insurance system, its differences and advantages from traditional insurance are analyzed. Also, based on international experience and statistical data, the legal, economic and social aspects of introducing Takaful in our country are considered and recommendations for development are given.